Changes in the polycrystalline gold electrode surface produced by square wave potential perturbations - Chialvo, Abel César (1984)
The electroreduction of gold oxide layers produced by a square wave potential signal (SWPS) under a proper set of perturbation conditions yields a reproducible electrode surface with a large increase in the surface area. The different variables are systematically investigated to establish the optimal conditions of the SWPS. The results are discussed on the basis of the thermodynamics and kinetics of oxide monolayer and multilayer formation.